Rhythm of the Seasons: Planting Seeds of Safety, Harvesting Grains of Hope -- A Lesson Plan for Farm Safety Audiences - Carol J. Lehtola; Charles M. Brown (EDIS)
This lesson plan is designed as the basis for the IMBY Farm and Home Hazard Workshop. IMBY stands for “In My Back Yard” — that is where safety should begin. The lesson plan gives direction for the educational part of the workshop. This document is CIR 1437, one of a series of Florida AgSafe, a program in the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published April 2003.